Canine urothelial carcinoma: expression of Periostin in spontaneous canine urothelial carcinoma and its correlation with histological features - Brambilla, Eleonora; Ciaputa, Rafał; Crepaldi, Paola; Dzimira, Stanislaw; Nowak, Marcin; Dziegiel, Piotr; Piotrowska, Aleksandra; Mollica Govoni, Veronica; Fonseca-Alves, Carlos Eduardo; Laufer-Amorim, Renée; Stefanello, Damiano; Romussi, Stefano; et al. (Frontiers in Veterinary Science, 2023)
The tumor microenvironment is considered one of the main players in cancer development and progression and may influence the behavior of cancer cells. Periostin (POSTN) is an extracellular matrix protein, and its main functions are induction of fibrillogenesis, fibroblastic cell proliferation and migration, enhancing regeneration in normal tissue, and promoting metastasis in case of neoplasia. POSTN has already been studied in humans in several normal tissues, inflammatory processes, and neoplasms, revealing an important role in tumor progression in various types of cancer, such as colon, lung, head and neck, breast, ovarian, and prostate. In these latter, high levels of POSTN are usually associated with a more aggressive tumor behavior, tumor advanced stages, and poor prognosis, while in human bladder urothelial carcinoma (BUC), unlike in most tumors, POSTN expression seems to be downregulated. The expression of this marker has been poorly investigated in veterinary medicine; thus, this study aimed to immunohistochemically investigate the presence and the intensity of POSTN expression in canine BUCs and to determine a possible relationship between POSTN expression and histopathological features such as mitotic count and muscular and vascular invasions. For the present retrospective study, archived samples from 45 canine BUCs and 6 non-neoplastic canine bladders were considered for histological evaluation and immunohistochemical examination for the expression of POSTN. POSTN expression was semi-quantitatively assessed considering both the percentage of the neoplastic stroma positive for POSTN and the intensity of the immunohistochemical labeling. Histologically, 38 out of 45 tumors were papillary and 7 out of 45 were non-papillary. All tumors were infiltrating, being that 21 were muscle-invasive, and a significant correlation between this feature and vascular invasion emerged (P = 0.0001). In normal bladder tissue, as reported in humans, a thick and strongly positive belt of POSTN was visible, and in canine BUCs, stating that the expression is comparable with human benign as well as malignant bladder tissue, a general decrease in POSTN expression was observed except for a strongly labeled ring of POSTN observed around some neoplastic nodules infiltrating the muscle layer. Moreover, POSTN expression and mitotic count were significatively inversely correlated (P = 0.0015). The fact that POSTN protein is less expressed in urothelial carcinomas than in the normal bladder supports what was reported in human BUCs and, together with the negative correlation between mitotic count and protein expression that emerged in the present retrospective study, encourages further prospective follow-up studies to verify the possible role of POSTN in canine BUCs as a prognostic marker, and also as a possible target for the development of future anticancer therapies.